Fetus in Fetu (Pre-surgical dilemma: Review of literature and a case report) - Sharma, Om Prakash; Shanmugam, Senthil (Asian Journal of Medical Sciences, 2011)
Fetus in fetu is an extremely rare developmental anomaly, due to disorganised embryogenesis in a diamniotic monochorionic pregnancy. Approximately 87 reports have been documented in the literature to date. We describe such an entity in two months old boy, who presented with abdominal distension and features of obstruction. Plain X ray abdomen and CT scan helped in correct pre operative diagnosis. The literature on this rare entity is reviewed, and the diagnosis and pathogenesis of the disease are discussed. Key Words: Fetus in fetu; CT scan; Teratoma; Axial skeleton; Diamniotic monochorionic twins DOI: 10.3126/ajms.v2i1.3208 Asian Journal of Medical Sciences 2 (2011) 68-71